Financial services in refugee hosting areas: Can they promote inclusion? Lessons from the SHARPE project in Ethiopia - de Brauw, Alan; Roy, Shalini; Tefera, Mulugeta (Centre of Excellence for Development Impact and Learning, 2022)
Digital financial inclusion is important to achieving the Sustainable Development Goals. Digital financial tools, such as mobile money, can, in principle, be used by anyone with a cell phone. There are several different ways that mobile money and services surrounding mobile money can help reduce poverty. For example, research demonstrates that mobile money helps increase remittances from labour migrants. It also helps households to weather negative shocks to income. In addition, it helps encourage investments whether on-farm or in self-employment activities.